2009
DOI: 10.1002/itdj.20115
|View full text |Cite
|
Sign up to set email alerts
|

Different spaces for e-development: What can we learn from the capability approach?

Abstract: "e-Development" is often pursued with a lot of thinking on the 'e' and little on the 'development,' rendering the link between them ambiguous and fragile. It is important to explicate what kind of "development" is being pursued, and how information and communication technology (ICT) can contribute to this goal. This article draws on Amartya Sen's capability approach to provide some theoretical reflections on e-development. It is argued that the capability approach, being a normative and evaluative approach, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
147
0
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(159 citation statements)
references
References 44 publications
0
147
0
12
Order By: Relevance
“…Sorensen et al 2007;Teale et al 2002;Açikalin 2009). In the extensive literature review (not reflected here) no evidence could be found of acknowledging input from ICT for Development and Information Systems theories -two fields that address, among other things, the successful adoption of ICT and related skills in developing communities (Chigona and Chigona 2010;Krishna and Madon 2003;Zheng 2009). Future literature reviews might also cover Information Behaviour and Adult Learning (Andragogy).…”
Section: Planning Guidelines For Information Literacy Training For Tementioning
confidence: 91%
“…Sorensen et al 2007;Teale et al 2002;Açikalin 2009). In the extensive literature review (not reflected here) no evidence could be found of acknowledging input from ICT for Development and Information Systems theories -two fields that address, among other things, the successful adoption of ICT and related skills in developing communities (Chigona and Chigona 2010;Krishna and Madon 2003;Zheng 2009). Future literature reviews might also cover Information Behaviour and Adult Learning (Andragogy).…”
Section: Planning Guidelines For Information Literacy Training For Tementioning
confidence: 91%
“…In conceptualising what constitutes development, we align ourselves with the capabilities approach [14][15][16]. We draw on existing research on capabilities and ICTD [17][18][19] to position our findings from the ANT framework within the broader discourse of development.…”
Section: Introductionmentioning
confidence: 99%
“…The CA suggests that impact evaluation may focus on the influence on people's capabilities to do and to be, on the quality of human life, and on the potential decrease in the obstacles in people's lives, to maximize everyone's freedom to live and choose the kind of life that they have reason to value (Sen, 2000). Therefore, the CA places the emphasis on the contribution that technologies may have to increase the capabilities (freedoms and opportunities) of individuals to function in their societies (Zheng, 2009). In this article, we present Sen's CA as one of the guiding frameworks through which to understand the complex link between ICT and Development.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in addition to providing ICT services, there is a need to create a social and institutional environment so that the poor and needy can access and assess information, build knowledge, and take decisions; in other words, enhance their basic capabilities. The CA calls for an alternative e-development beyond the space that centers on economic growth or modernization (Zheng, 2009). Alternative e-development should focus on the space of substantive freedom where ICT may add to development by influencing a change in the quality of life through the innovation and diffusion of human-oriented technologies.…”
mentioning
confidence: 99%
See 1 more Smart Citation